Sources of law of the European administrative space in the context of cultural rights of citizens - Юринець, Юлія Леонідівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
A system of sources of law in force within the European administrative space in the field of cultural rights of citizens who (sources) should serve as a guide in the implementation of the principles, norms and standards of the European administrative space in the national legislation of Ukraine. The relationship of these processes with the European integration challenges facing Ukraine.